Flexible flow shop scheduling for continuous production. (2016) - Sokolov, Boris; Ivanov, Dmitry; Potryasaev, Semyon A.
Flexible flow shop problem is represented as the dynamic interpretation of scheduling based on a natural dynamic decomposition of the problem and its solution with the help of a modified form of continuous maximum principle blended with combinatorial optimisation. A theoretical analysis of optimal scheduling approach with uniform alternative machines is considered. The scheduling approach is based on a dynamic non-stationary interpretation of the job execution and a temporal decomposition of the scheduling problem. The optimality conditions as well as the structural properties of the model and the algorithm are investigated. Advantages and limitations of the proposed approach are discussed. The results of this study can be used as an extension to the existing mathematical programming models subject to the following issues: dynamics and non-stationarity of the operation execution, non-stationarity of the machine structures and capacity parameters, and representation of continuous flows. In addition, the formulation of the scheduling model in terms of control makes it possible to attract additional tools from mathematics of functional spaces such as stability, robustness, controllability, adaptability, etc. to the schedule analysis and real-time adjustment.